Parasitemia and Associated Immune Response in Pregnant and Non-Pregnant Beef Cows Naturally Infected With Neospora caninum - Gual, Ignacio; Campero, Lucía María; Hecker, Yanina Paola; Regidor-Cerrillo, Javier; Leunda, María Rosa; Odeón, Anselmo Carlos; Campero, Carlos Manuel; Torioni de Echaide, Susana; Echaide, Ignacio Eduardo; Estein, Silvia Marcela; Ortega-Mora, Luis Miguel; Moore, Dadín Prando (Frontiers in Veterinary Science, 2022)
The aim of this longitudinal study was to characterize the parasitemia of Neospora caninum and the associated immunological parameters in naturally infected beef cows for a period of 10 months. The following groups were established: Neospora caninum seropositive pregnant cows (+Preg, n= 7), seropositive non-pregnant cows (+Npreg, n= 7), seronegative pregnant cows (-Preg, n= 4) and seronegative non-pregnant cows (-Npreg, n= 4). Several samples were obtained for absolute and relative leukocyte counting, cytokines IL-10, IL-12, α-TNF and γ-IFN quantification, specific IgG, IgG1 and IgG2 and avidity and N. caninum DNA molecular detection and quantification. The +Preg group had higher frequency and concentration of N. caninum DNA in PBMC in the last third of pregnancy compared to +Npreg (p<0.05), with 22% and 8% of detection, respectively. Parasitemia correlated positively with IgG titers and negatively with IgG1/IgG2 ratio (p<0.05). On day 222 of the assay, the +Preg group had the lowest total leukocyte counting (p<0.05). The +Preg group had higher concentration of IgG and higher avidity in the last third of gestation compared to +Npreg (p<0.05). Avidity correlated with total IgG and IgG2 (p<0.05). All +Preg cows gave birth to clinically healthy but seropositive calves before colostrum intake, therefore, congenital transmission was 100% efficient. Only a complete N. caninum genotype from a placenta and a partial genotype from cow #3 of the group +Preg was achieved by multilocus microsatellite analysis. Over all, N. caninum parasitemia is frequent in seropositive beef cows during the last third of gestation. This correlates with higher antibody levels and a decrease of total leukocyte counting. The precise timing of the parasitemia may be used for diagnosis purposes and/or for design strategies to avoid vertical transmission. Further studies are needed to identify the immune molecular mechanisms that favor parasitemia during gestation in chronically infected cattle.